Analisis Tingkat Kebangkrutan pada PT Patra Trading Jakarta - Melania Chaterine Marpaung (Yayasan Literasi Sains Indonesia, 2024)
This research aims to determine the prediction of the bankruptcy level of PT. Patra Trading uses financial report data from 2021 to 2023. The method used in this research is Quantitative Descriptive non-Statistical. This research uses secondary data originating from the company PT Patra Trading in the form of the company's annual financial report. The population used is a subsidiary of PT Pertamina Patra Niaga. The sampling technique used in this research is Purposive Sampling for taking samples from the population based on certain criteria. The benchmarks for this bankruptcy prediction analysis consist of several ratios; (1) working capital to total asset; (2) rentaint to total asset; (3) profit before interest and tax to total assets; (4) book value equity to book value liquiditas; (5) profit before tax on current liabilities; (6) sales to total assets: (7) return of assets; (8) debt ratio; (9) current ratio. The results of the analysis using the Altman Z-Score, Springate, Zmijewski, Grover model on PT Patra Trading, provide different research results, where two of them say that PT Patra Trading is in the healthy category, namely in the Zmijewski model the final figure for this model is below 0 and the Grover model final figure is above 0.001. The Springate model says that PT. Patra Trading is still in the bankruptcy category where the final figure is below the standard, namely 0.862. Finally using the Altman Z Score model at PT. Patra Trading is in the gray area.